Does cochleostomy location influence electrode trajectory and intracochlear trauma?. (27th October 2014) - Zhou, Ling; Friedmann, David R.; Treaba, Claudiu; Peng, Robert; Roland, J. Thomas
Abstract : Objectives/Hypothesis: Trauma to intracochlear structures during cochlear implant insertion is associated with poorer hearing outcomes. One way surgeons can influence insertion trauma is by choosing the surgical approach. We seek to compare cochleostomy (CO), peri–round window (PRW), and round window (RW) approaches using a fresh frozen temporal bone model. Study Design: Experiments using fresh frozen temporal bones. Methods: Cochlear implant insertions using the three aforementioned approaches were performed on 15 fresh frozen human temporal bones using a Cochlear 422 electrode. Insertions were evaluated by examining fluoroscopic recordings of histologic sections. Results: Five cochlear implant insertions were performed using each of the three aforementioned approaches. Fluoroscopic examination revealed that none of the CO or PRW insertions contacted the modiolus during insertion, whereas three of five RW insertions did. RW insertions were less linear during insertion when compared to CO and PRW insertions ( P  < .05). CO insertions had significantly larger angular depth of insertion (487°) when compared to PRW (413°) and RW (375°) ( P  < .05). Histologic examination revealed one RW insertion resulted in osseous spiral lamina fracture, whereas the remaining insertions had no evidence of trauma. In the damaged specimen, the inserted electrode was observed to rest in the scala vestibuli, whereas the remaining electrodes rested in the scala tympani. Conclusions: Due to variability in RW anatomy, a CO or PRW window surgical approach appears to minimize the risk for insertion trauma. However, with favorable anatomy, a Cochlear 422 electrode can be inserted with any of the three approaches. Level of Evidence: NA Laryngoscope, 125:966–971, 2015